Contributions of Muhammad Baqir Al-Majlisi to the Cultural life during the Safavid era (Journal of the College of Basic Education, 2025)
The research talks about the personality of Muhammad Baqir al-Majlisi, the great diligent scholars, for his intellectual and religious heritage, as he was considered an example of a prominent figure in the Safavid era, and the purpose of the research is to review the history of al-Majlisi and his contributions to cultural life during his work in the Safavid era, and determine the time frame of the subject of the study in the Safavid era (1627 AD - 1698). The aim of this study was to highlight the contributions of Muhammad Baqir al-Majlisi to the cultural life of the Safavids. The researcher relied on the descriptive narrative approach in narrating historical events by collecting scientific material and describing it in an objective scientific manner. The researcher reached several results, including (Muhammad Baqir al-Majlisi occupied a great position in the Safavid state, Muhammad Baqir al-Majlisi left an impact on the religious, social and cultural life of the Safavid state, as his writings that he left were of great importance, Muhammad Baqir al-Majlisi had a moderate style between fundamentalism and news, and devoted his life to spreading the narrations of the infallible imams (peace be upon them), Muhammad Baqir al-Majlisi was distinguished from all other scholars of his time In the field of authorship and writing, especially in the field of the Persian language